Communication and differentiation between commercial footwear v conceptual footwear through semiotics analysis - Broega, A. C. (2012)
Fashion communication occurs through images, shapes, and cultural values, leading individuals to feel the need to "belong" to a particular group. This article investigates the communication and differentiation between commercial footwear V conceptual analysis, through semiotic analysis. For such differentiation could be studied, it was made a brief study on semiotic analysis, settling some points to be analyzed in commercial and conceptual images of footwear in order to demonstrate this differentiation. The result of this analysis shows that the interpreter differentiates the products by several aspects, determining which one to use and the other as conceptual or symbolic object that favors the concept in detriment of the use or sellable.